Software development for real time data capturing and least square estimation analysis - Abbas, Mohd. Azwan (2005)
Industrial survey is a discipline of engineering surveys that requires the utmost in achievable accuracies and real time data processing. The instrumentation used in conventional industrial survey requires long painstaking procedures with very skilled craftsmen to obtain the required results. Revolution of technology with the introduction of new instruments (such as total station, computer and software) has revolutionized industrial survey. The development of three dimensional (3D) coordinating system and total station interfaced to a microcomputer provides the capabilities for on line data gathering with simultaneous processing in 3D. This research concentrates on the development of software to capture data (from total station) in real time. Least Square estimation (LSE) process is also performed on the data. For this purpose, robotic tachometry system TCA 2003 is used as a sensor and Microsoft Visual Basic V6.0 is used to develop the software.